Career of horizontal education mismatch workers: career competency, job crafting, and work engagement - Laila Meiliyandrie Indah Wardani; Dyah Ayu Sekarini; Rahmat Dwi Syaputra; Mayang Safira Kartikawati; Rizki Dawanti; Dian Din Astuti Mulia; Mohd Dahlan A. Malek (Intelektual Pustaka Media Utama (IPMU) in collaboration with Institute of Advanced Engineering and Science (IAES), 2021)
Education is one of many factors that has the biggest impact toward unemployment rate due to the fact that there are mismatches between educational background and the intended job, and it is named horizontal education mismatch. The employee who is run into educational mismatch condition is seen less-competent, less-qualified, and less accomplished associated with company and work engagement which should be owned by every employee, both supervisors and subordinates. The purpose of this study was to test out that Job Crafting can play a role as a relation mediator between career competencies and work engagement toward employees which run into horizontal education mismatch. This was quantitative research; with purposive sampling method to recruit the respondent. The respondent of this research was people with age range 17-65 years old and using Process v3.5 by Hayes, The Simple Mediation Model No.4. Considering the phenomenon of Horizontal Education Mismatch which has an impact on competency and work engagement. The uniqueness of this research was to pay attention to the suitability of educational background with the current occupation, which indirectly affects the competence of workers. The results of this study were in accordance with the aims and expectations of the researchers. The results of this study indicated that job crafting plays a role as a mediator in the correlation between career competencies and work engagement. Hopefully, it will be able to meet the competency needs of employees to increase employee engagement with the company.